The Geopolitical Concept of Information Warfare in the Russian Social Thought - Yury Vasilyevich Kosov; Yulia Vladimirovna Vovenda (Управленческое консультирование)
The article is considered geopolitical concept of well-known scholars Y.N. Panarin and A.G. Dygin. The main attention is paid to information war and the forming of the new union of state (Eurasian zone). There is the analysis of the concept of the “Eurasian net” that is based on the theory of “net wars”.